Advancement of Total Ammonia Nitrogen Removal Technologies for Urban/Peri-Urban and Rural Wastewater Treatment - Chen, Huiyu (Université d'Ottawa / University of Ottawa, 2022)
Due to the adverse effects of ammonia on the environment, many governments, including Canada, have imposed new regulations to reduce the discharge of ammonia wastewater effluent into natural receiving waters, which has resulted in the upgrade of ammonia removal at water resource recovery facilities (WRRFs) across the world. There is therefore a need to investigate present urban/peri-urban and rural challenges associated with municipal total ammonia (TAN) removal. In particular, there is a need to further advance and optimize technologies such as the moving bed biofilm reactor (MBBR) to meet these critical challenges. The first objective of this thesis is to validate an elevated loaded strategy for partial nitritation (PN) MBBR as an application for mainstream urban and peri-urban municipal wastewater treatment and to elucidate the mechanism of nitrite-oxidation suppression of this system. The second objective is to identify practical storage strategies for nitrifying MBBR units as rural municipal wastewater upgrade systems (lagoon systems), optimizing the TAN removal performance during seasonal discharge periods. In the context of the present climate change crisis and sustainable development requirements, there is an increased need for efficient TAN removal from urban and peri-urban municipal wastewaters. The application of the energy and cost-efficient partial nitritation/anammox (PN/A) technology to mainstream urban and peri-urban municipal wastewater can prove challenging because of limited ability to achieve the stable PN. Hence, there is a need for the validation of the present strategies for achieving effective and stable PN in the mainstream portion of conventional urban and peri urban WRRFs. The 45 days operation of a laboratory-scale, elevated loaded PN MBBR with average surface area loading rate (SALR) of 5.2 ± 0.1 g TAN/m²·d and a hydraulic retention time of 2h showed a successful and stable nitrite accumulation. The average surface area removal rate (SARR) of 2.3 ± 0.2 g TAN/m²·d (theoretical performance objective of 2.7 g TAN/m²·d), TAN removal efficiency of 43.1 ± 3.4% (theoretical performance objective of 53%) and NO₂- / (NO₂- + NO₃-) ratio of 82.4 ± 4.8% (theoretical performance objective of 100%) meets the necessary requirement to support subsequent cost-efficient anammox process. Biofilm analyses of the laboratory-scale, elevated loaded PN MBBR indicated that the attached biofilm was thick and dense, stable biofilm that did not show and biofilm loss or washout. Biofilm cell viability analyses was indicative of an active biofilm. The ratio of AmoA gene targets of the ammonia oxidizing bacteria (AOB) in the MBBR biofilm to the targeted gene region of the Nitrospira nitrite oxidizing bacteria (NOB) population demonstrates that NOB activity suppression of this technology was the dominant mechanism of nitrite-oxidation in the elevated loaded PN MBBR system. In North America, the TAN removal performance of waste stabilization ponds (also termed wastewater treatment lagoon systems), which are widely applied as rural WRRFs, is often not stable due to seasonal temperature variations. Nitrifying MBBR as an upgrade TAN removal unit has been successfully applied to improve TAN removal during winter. However, re-seeding the nitrifying MBBR biofilm during each seasonal operation period is not sustainable. There is therefore an urgent need for optimizing storage strategies of nitrifying MBBR carriers when used as TAN removal upgrade systems of rural WRRFs. The study of storage strategies for nitrifying MBBR as lagoon upgrading systems indicated the batch storage of the nitrifying MBBR biofilms with intermittent aeration could be an effective storage strategy for short-term (12 weeks) storage. Carriers stored in continuous flow aerated condition was shown to be the second most suitable storage method for nitrifying MBBR carriers for systems exposed to less than 12 weeks of storage. Carriers stored in dry condition, batch aerated conditions without flow, and continuous flow aerated condition for long-term (over 18 weeks) failed to achieve full nitrification following 18 days of operation conditions. Carriers stored in dry condition did not successfully achieve full nitrification for short-term and long-term storage and may not be applied to store full nitrification MBBR carriers. The study suggested that, compared to re-seeding start up strategy of the lagoon upgrading nitrifying MBBR biofilm, the use of the appropriate storage strategies, such as batch aerated conditions without flow, has the potential to shorten the start-up time and save energy during the non-discharge periods.
Keywords: Ammonia oxidizing bacteria; Anammox; Biofilm characteristic; Nitrite oxidizing bacteria; Start-up strategy